Establishment of a standard reference material (SRM) herbal DNA barcode library of Vitex negundo L. (lagundi) for quality control measures. Issue 5 (3rd May 2016) - Olivar, Jay Edneil C.; Alaba, Joanner Paulus Erik P.; Atienza, Jose Francisco M.; Tan, Jerick Jeffrey S.; Umali, Maximo T.; Alejandro, Grecebio Jonathan D.
ABSTRACT: The majority of the population in the Philippines relies on herbal products as their primary source for their healthcare needs. After the recognition of Vitex negundo L. (lagundi) as an important and effective alternative medicine for cough, sore throat, asthma and fever by the Philippine Department of Health (DOH), there was an increase in the production of lagundi-based herbal products in the form of teas, capsules and syrups. The efficiency of these products is greatly reliant on the use of authentic plant material, and to this day no standard protocol has been established to authenticate plant materials. DNA barcoding offers a quick and reliable species authentication tool, but its application to plant material has been less successful due to (1) lack of a standard DNA barcoding loci in plants and (2) poor DNA yield from powderised plant products. This study reports the successful application of DNA barcoding in the authentication of five V. negundo herbal products sold in the Philippines. Also, the first standard reference material (SRM) herbal library for the recognition of authentic V. negundo samples was established using 42 gene accessions of ITS, psbA-trnH and matK barcoding loci. Authentication of the herbal products utilised the SRM following the BLASTn and maximum-likelihood (ML) tree construction criterion. Barcode sequences were retrieved for ITS and psbA-trnH of all products tested and the results of the study revealed that only one out of five herbal products satisfied both BLASTn and ML criterion and was considered to contain authentic V. negundo . The results prompt the urgent need to utilise DNA barcoding in authenticating herbal products available in the Philippine market. Authentication of these products will secure consumer health by preventing the negative effects of adulteration, substitution and contamination.